Oroantral communication - A clinical and radiographic retrospective study of 39 Iraqi patients (Mustansiria Dental Journal, 2018)
Background: oroantral communication (OAC) is abnormal connection between oralcavity and maxillary sinus. OAC is a rare, well known complication, mostlyoccurs after the extraction of upper posterior teeth, and if not treated lead toformation of oroantral fistula (OAF) and many complications .surgical repair isvery necessary to prevent further complications .The aim of this study to evaluateand analyze the clinical, radiographic aspects of 39 Iraqi patients with oroantralfistula.Materials and methods :the study was carried on 39 patients with oroantral fistulareported to the Department of oral and maxillofacial surgery ,college of dentistry,University of Baghdad ,and private practice from 1983 to 2010 .data regarding theage ,sex , cause ,site ,radiographic features and types of radiographs ,signs andsymptoms ,duration ,relation to the adjacent teeth , sinus disease ,methods oftreatment .Results: 39 cases of OACs, 26 male, 13 female, the age range was20-65 with a meanage 44.5 year. Highest incidence was seen in the third and fourth decade of life61.4%. The highest frequency of OACs was seen in relation to upper first molar48.7% .the commonest cause was complicated extraction 51.2% .pain andtenderness was the most prominent symptoms 80%, escape of fluid from the nosewas the most prominent sign 75.6%.there was a long delay in the diagnosis andtreatment .most of the OACs occurs near the edentulous areas, occipitomentalradiograph was not reliable in detection of displaced roots. Buccal advancementflap was the main method in treatment 81.2%.Conclusions: OACs a rare complication, its management need good clinical andradiological experience, and the treatment should be individualized to have goodresults.